Physiologic effects of caffeine on cross-country runners - Birnbaum, L. J.; Herbst, J. D. (The Journal of Strength and Conditioning Research, 2004)
This study determined the physiological effects of caffeine on cross-country runners during submaximal exercise. Ten college-age subjects (5 women; 5 men) volunteered to participate in this study. After completing a O2max test, each subject completed 2 30-minute runs at 70% O2max on the treadmill, 1 after ingesting caffeine and the other after ingesting a placebo. A caffeine dosage of 7 mg·kg-1 of body weight was administered. The same dosage of vitamin C was used as a placebo. The order of treatments was randomly assigned, and the trials followed a double-blind format. The physiological data were analyzed using a repeated measures analysis of variance (SPSS). Tidal volume (TV), alveolar ventilation (VA), and rating of perceived exertion (RPE) were significantly different (p < 0.05) between treatment and control groups. The results suggest that the ingestion of caffeine at 7 mg·kg-1 of body weight prior to submaximal running might provide a modest ergogenic effect via improved respiratory efficiency and a psychological lift.